Endogenous levels and exogenous application of glycinebetaine to grapevines - Mickelbart, Michael V.; Chapman, Peter; Collier-Christian, Lucy (Scientia horticulturae, 2006)
Glycinebetaine (GB) plays a role in stress tolerance in many plant species that synthesize this compatible solute; however, many plants are unable to naturally synthesize GB or synthesize very low levels. In an effort to increase stress tolerance, there have been attempts to artificially increase the concentration of GB in plants by selection for high accumulating species, genetic engineering, or exogenous application. Grape is an economically important temperate zone fruit species that is subject to multiple environmental stresses, such as temperature extremes, that lead to reductions in fruit yield and quality. Application of GB to grapevines at critical periods (e.g. prior to spring frosts) may protect plants and maintain yields. We examined endogenous levels of GB, and the effects of exogenous GB on growth and physiology of grapevine. Field-grown plants had very low endogenous levels of GB. There was no consistent genetic variation for GB either among a set of 13 cultivars or clones of Chardonnay or Pinot noir. Application of GB to plants grown in a controlled environment slightly reduced growth rates, resulting in a lower shoot leaf area at concentrations of 50, 100, or 200 mM. Application of GB also increased the average number of days to maximum leaf area, and increased specific leaf weight. Concentrations of 100 or 200 mM resulted in growth cessation and phytotoxicity. Leaf osmotic potential decreased only slightly with GB application. Leaf water potential and leaf relative water content were unaffected by GB. Photosynthetic rate of GB-treated plants increased in one experiment, but overall, our results reflect previous work indicating that GB has little or no affect on physiological parameters in non-stressed plants. We have established endogenous GB levels in grape and non-toxic application levels for further work on the potential effects of GB on grapevine stress tolerance.